Normalising community-led, empowered, disaster planning: Reshaping norms of power and knowledge - Margot Rawsthorne; Amanda Howard; Pam Joseph (Oñati Socio-Legal Series)
Disasters (and the dynamics that proceed and follow them) are inherently disruptive of customary routines and taken for granted ordinariness. Many fear that in the context of climate change disasters will become “the new norm”. How we prepare for, respond to, and recover from disasters provide a rich terrain for exploring “normality” and interrogating normalising processes. In this article we draw on insights from empirical research on policy efforts in disaster preparedness in New South Wales, Australia. This research suggests that understandings of “the norm” is a site of contestation. This discursive debate is most evident in policy and practice prescriptions for “shared responsibility”. International and national policy is shifting responsibility for disaster preparedness away from institutions of the State to the individual within the local community. In practice, we see this shift simultaneously resisted and embraced with “norms” in disasters reshaped in multiple sites and in multiple directions. The paper concludes that engagement in complex debates offers the possibility to disrupt traditional pattens and normalise community-led, empowered, responses to disasters.